I would like to show that

If M is martingale, then $$E[M_n] = E[ M_0]$$ for all n.

What I have done is

As we know the definition of martingale, $E[ M_{n+1} | F_n] = M_n$

By using this definition, I have firstly shown that $M_{n+k}$ replace $M_{n+1}$.

That’s, I have $E[ M_{n+k} | F_n] = M_n$

By the law of total expectation, I get

$$ E[M_{n+k}]= E[ M_{n+k} | F_n] = E[M_n]$$

so I assume n=0, I have

$$ E[M_{0+k}]= E[ M_{0+k} | F_0] = E[M_0]$$

i.e. $E[M_k]=E[M_0]$

where I may accept $k=n$.


I did this proof in order to show the statement in the yellow box.

But, the proof which I did seems trivial to me. I would like to learn the actual proof of the statement.

Thank you for your helps.


\begin{align*} {\mathbb E}[M_{n}] ={\mathbb E}[{\mathbb E}[M_{n}|{\mathcal F}_{n-1}]] ={\mathbb E}[M_{n-1}] =\cdots ={\mathbb E}[M_{0}]. \end{align*}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.